Tampilan elongasi prosesus styloid pada pasien dengan gangguan sendi temporomandibula - Fitri Angraini Nasution; Azhari Azhari; Fahmi Oscandar (Jurnal Radiologi Dentomaksilofasial Indonesia (JRDI), 2020)
Objectives: The purpose of this case report was to report the finding of styloid process morphology in patients with TMD. Case Report: A 22-years-old female patient came to the radiology installation of Rumah Sakit Gigi dan Mulut Unpad Bandung for a Cone Beam Computed Tomography – 3 Dimension (CBCT-3D) examination with a clinical diagnosis of temporomandibular joint disorders (TMD). CBCT-3D examination results showed a change in the shape and position of the right and left condyle head. The length of the styloid process from the sagittal view on the right side was 34,0 mm and the left side 35,0 mm with the elongation type styloid process according to Langlais et al on the right and the left sides were elongated (type I). The styloid process undergoes bilateral elongation with the same type of elongation between the right and the left sides. Angulation of the styloid process from the coronal view on the right side was 68,6° and the left side 55,9°. There was a change in the shape of the right and left styloid processes from the axial view at the temporal base, middle and the tip of styloid process. Conclusion: TMD provides an abnormality in elongation of styloid process, CBCT is an effective diagnostic imaging modalities in evaluation of styloid process length.